Perancangan Interior Pusat Perlengkapan dan Hiburan Anak di Surabaya - Amanda, Gabrile Saretta (Intra, 2015)
Surabaya City is the second largest city that presents high prospects in trade and setting up businesses. Seen from the peopleâs lifestyle, especially in the matters of fashion which is a human basic need. Fashion grows in line with trend, nor among children. Childrenâs needs become a priority for parents, like their equipment, entertainment, and education so that increases the need of facilities provided for the children. Because of the absence of a retail which facilitates all the needs of children at the same time, this design aims to give facilities in shopping, playing and learning at once. Retail not only becomes a place for shopping but also to fulfill the need of new experience and the mood in entertainment and education that impacts positively on children development.